Plant-Mediated Zinc Oxide Nanoparticle and Copper Doped Zinc Oxide Nanocomposite for Photocatalytic Degradation of Methylene Blue Dye - Pokhrel, Pratikshya; Nyachhyon Rajbhandari, Armila (Journal of Institute of Science and Technology, 2025)
Green synthesis of zinc-oxide (ZnO) nanoparticles and copper-doped zinc oxide (Cu-ZnO) nanocomposites were carried out by treating zinc nitrate and copper nitrate precursors with aqueous extract of Cinnamomum camphora leaves powder. X-ray diffraction spectroscopy (XRD), Fourier transform infrared spectroscopy (FTIR), Scanning electron microscopy (SEM), and UV-visible spectrophotometry have been used to characterize the prepared materials. XRD analysis showed that both materials are crystalline in nature. The average crystallite size of ZnO and Cu-ZnO was found to be 21 nm and 17.51 nm, respectively. The FTIR spectra displayed clear bands of ZnO at 508.1 cm-1. The SEM image demonstrated crystalline circular patch like morphology for both nanoparticles and the UV-visible spectra displayed a characteristic absorption band at 378 nm for ZnO and 382 nm for Cu-ZnO. The synthesized ZnO nanoparticles and Cu-ZnO nanocomposites have been used to degrade methylene blue (MB) under UV light. Cu-ZnO nanocomposites showed 98 % MB degradation within 240 minutes at pH 10 while only 90 % MB dye was degraded by ZnO nanoparticles. Results revealed that the optimum catalyst dose was 30 mg and dye concentration was 5 mg/L along with 0.4 mL of 1% H2O2. In this study, it has been demonstrated that Cu-doped ZnO displayed excellent photocatalytic efficiency towards degradation of dye within a short period of time even in low concentration.